2013
DOI: 10.1016/j.cor.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Push-relabel based algorithms for the maximum transversal problem

Abstract: We investigate the push-relabel algorithm for solving the problem of finding a maximum cardinality matching in a bipartite graph in the context of the maximum transversal problem. We describe in detail an optimized yet easyto-implement version of the algorithm and fine-tune its parameters. We also introduce new performance-enhancing techniques. On a wide range of realworld instances, we compare the push-relabel algorithm with state-of-the-art algorithms based on augmenting paths and pseudoflows. We conclude th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Hence, we set iterGR to 0 (line 3 of Algorithm 3) which stores the iteration number in which the next global relabeling will be performed. Experiments in the literature show that the performance of the algorithm changes drastically with the strategy to set iterGR [7], [16]. In our preliminary experiments, we also observed this sensitivity with different implementations of GETITERGR (line 7 of Algorithm 3).…”
Section: Algorithm 4 G-gr: Gpu-based Global Relabelingsupporting
confidence: 49%
See 4 more Smart Citations
“…Hence, we set iterGR to 0 (line 3 of Algorithm 3) which stores the iteration number in which the next global relabeling will be performed. Experiments in the literature show that the performance of the algorithm changes drastically with the strategy to set iterGR [7], [16]. In our preliminary experiments, we also observed this sensitivity with different implementations of GETITERGR (line 7 of Algorithm 3).…”
Section: Algorithm 4 G-gr: Gpu-based Global Relabelingsupporting
confidence: 49%
“…For example, it has been shown that when the active columns are visited with a FIFO order, the push-relabel approach obtains a better performance. The most recent implementation and a comparison with the augmenting-path-based algorithms are given by Kaya et al [7]. The authors showed that PR is slightly better than the augmenting-path-based algorithms.…”
Section: Algorithm 2 Gr: Global Relabelingmentioning
confidence: 99%
See 3 more Smart Citations